Implikasi Kebijakan Otonomi Daerah terhadap Pengelolaan Lembaga Pendidikan Islam - mugiarto, mugiarto; Wasliman, Iim; Handayani, Sri (Jurnal Kridatama Sains dan Teknologi, 2022)
Madrasah performance dominantly to date is very low and below the standard of other educational institutions. Only a small number of Islamic education are able to compete with other educational institutions. Seeing such a phenomenon is interesting to conduct an assessment of the conditions and problems that are actually faced by Islamic education institutions in Indonesia. Research is a literature research with the focus of the study of the implications of regional autonomy policies in the management of Islamic educational institutions, while the object to be studied is the implications of the regional autonomy policy in the management of Islamic educational institutions, with the procedure for obtaining data on researchers using literature. The data obtained will be identified, examined, analyzed, and interpreted so that the substance of the implications of regional autonomy policies in the management of Islamic educational institutions can be captured. After that, researchers will try to compare with other theories, to achieve a complete picture of the implications of regional autonomy policies in the management of Islamic educational institutions. The results of the study that the presence of madrasas in Indonesia has the same duties and roles as schools. As an educational institution that prepares the young generation of Muslims for the future, madrassas are expected to be able to produce graduates who will be able to play an important role in all sectors of national life, both the religious, social, economic, political, scientific and technology sectors. Madrasas are seeded than public schools because madrasas provide religious education (which is better than public schools) in addition to public education (which is the same as public schools). The problem that is still faced by madrasas today is the still low quality standards of general education provided in madrasas. Problems in the management of Islamic educational institutions in Indonesia faced, are (1) management problems which include the field of human resources/education personnel, curriculum fields, facilities and infrastructure; (2) Conceptual-Teoritis and Operational-Practical Problems; and (3) the problem of education policies and politics. Keywords: Implications, Regional Autonomy, Madrasa, Problems, Solutions